Life Cycle Assessment and Tool Development for Evaluating the Environmental Impact of Plastics - Malin, Matias (My University, 2026)
This thesis presents a life cycle assessment (LCA) of selected plastic materials used in LED lighting optics. The study was conducted to assess the environmental performance of products and identify the most important factors affecting their life cycle impacts. The assessment was conducted in accordance with ISO 14040 and ISO 14044 standards. The system boundary was defined as cradle-to-grave, excluding the use phase of the finished product. The analysis focused on global warming potential, water consumption and the share of renewable and non-renewable energy sources. Life cycle inventory data were collected from primary and secondary sources, and the environmental impacts were calculated using an LCA-evaluation tool. The results showed that raw material production dominates the overall environmental impacts with all three assessed materials. The impact of the product manufacturing phase on the total environmental impact is relatively small, although the choice of energy source has some impact on the total carbon environmental impacts. The findings show the importance of material selection, use of recycled materials and renewable energy sources in reducing the environmental impacts of plastic products. Results from the LCA can be used to support decision-making and improving sustainability by examining the environmental impacts of each life cycle.

Tässä diplomityössä esitetään elinkaariarviointi (LCA) valituista LED-valaistuksen optiikassa käytettävistä muovimateriaaleista. Tutkimuksen tavoitteena oli arvioida tuotteiden ympäristösuorituskykyä sekä tunnistaa keskeisimmät tekijät, jotka vaikuttavat niiden elinkaaren aikaisiin ympäristövaikutuksiin. Arviointi toteutettiin ISO 14040- ja ISO 14044-standardien mukaisesti. Tarkastelun järjestelmärajaukseksi määriteltiin cradle-to-grave-lähestymistapa siten, että valmiin tuotteen käyttövaihe rajattiin tarkastelun ulkopuolelle. Analyysi keskittyi ilmaston muutosta vauhdittavien päästöjen, veden kulutuksen sekä uusiutuvien ja uusiutumattomien energianlähteiden osuuteen. Data kerättiin sekä ensisijaisista että toissijaisista lähteistä ja ympäristövaikutukset laskettiin LCA-arviointityökalun avulla. Tulokset osoittivat, että raaka-aineiden tuotannosta aiheutuu suurimmat ympäristövaikutukset kaikilla kolmella materiaalilla. Tuotteen valmistusvaiheen vaikutus kokonaisympäristövaikutuksiin on suhteellisen pieni, vaikka käytetyn energianlähteen valinnalla on vaikutusta ilmastovaikutuksiin. Tulokset osoittavat materiaalivalintojen, kierrätettyjen materiaalien käytön sekä uusiutuvien energianlähteiden merkityksen muovituotteiden ympäristövaikutusten vähentämisessä. Elinkaariarvioinnin tuloksia voidaan hyödyntää päätöksenteon tukena ja kestävyyden kehittämisessä tarkastelemalla tuotteen elinkaaren eri vaiheiden ympäristövaikutuksia.
Keywords: Life Cycle Assessment; Plastics; Sustainable Materials; Sustainability